Adolescent vulnerabilities and opportunities: constructivist developmental perspectives - Amsel, Eric; Smetana, Judith (Interdisciplinary approaches to knowledge and development, 2011)
This book explores the central importance of adolescents' own activities in their development. This focus harkens back to Jean Piaget's genetic epistemology and provides a theoretically coherent vision of what makes adolescence a distinctive period of development, with unique opportunities and vulnerabilities. An interdisciplinary and international group of contributors explore how adolescents integrate neurological, cognitive, personal, interpersonal and social systems aspects of development into more organized systems.